Answer:
15
Step-by-step explanation:
2(2) - 18 = -14 |-14| = 14
3(2) -7 = -1 |-1| = 1
14+1=15
Answer:
15
Step-by-step explanation:
Answer:
-5(g-3h+5)
Step-by-step explanation:
-5g+15h-25
-5(g-3h+5)
Answer:x = 1
y = 1
Step-by-step explanation:
The given system of simultaneous equations is expressed as
3x - 5y = - 2 - - - - - - - - - - - - 1
2x + y = 3 - - - - - - - - - - - - - 2
The first step is to decide on which variable to eliminate. Let us eliminate x. Then we would multiply both rows by numbers which would make the coefficients of x to be equal in both rows.
Multiplying equation 1 by 2 and equation 2 by 3, it becomes
6x - 10y = - 4
6x + 3y = 9
Subtracting, it becomes
- 13y = - 13
y = - 13/- 13 = 1
The next step is to substitute y = 1 into any of the equations to determine x.
Substituting y = 1 into equation 2, it becomes
2x + 1 = 3
2x = 3 - 1 = 2
x = 2/2 = 1
Answer:
5 , -7 , 10
Step-by-step explanation: